Microgravity Effect on Microstructural Development of Tri-calcium Silicate (C3S) Paste - Moraes Neves, Juliana; Collins, Peter J.; Wilkerson, Ryan P.; Grugel, Richard N.; Radlińska, Aleksandra (Frontiers in Materials, 2019)
For the first time, tricalcium silicate (C3S) and an aqueous solution were mixed and allowed to hydrate in the microgravity environment aboard the International Space Station (ISS). The research hypothesis states that minimizing gravity-driven transport phenomena, such as buoyancy, sedimentation, and thermosolutal convection ensures diffusion-controlled crystal growth and, consequently, lead to unique microstructures. Results from SEM micrographs, image analysis, mercury intrusion porosimetry, thermogravimetry, and x-ray diffraction revealed that the primary differences in g hydrated C3S paste are increased porosity and a lower aspect ratio of portlandite crystals, likely due to a more uniform phase distribution. Relevant observations led by the presence or absence of gravity, including bleeding effect, density, and crystallography are also presented and discussed.